TINGKAT POPULARITAS DAN PROFITABILITAS MENU MELALUI METODE MENU ENGINEEERING DI RESTORAN PECEL LELE KHATIB PADANG - Kumalasari, Diah Oktryanti; Waryono, Waryono; Pasaribu, Pasaribu (Journal of Home Economics and Tourism, 2017)
This research aims to knows the level of popularity and profitability of the menu through the engineering menu method at Pecel Lele Restaurant Khatib Padang. This research is descriptive research with quantitative data. The sample in this research is sales data from January to May 2016 and processed using menu engineering worksheet. Data collection is had by interview, observation and documentation. The results of this study indicate that: (1) The menu that has the popularity of pecel lele, pecel ayam, soto betawi, fried rice, apple juice, avocado juice, guava juice, orange juice, mango juice, soursop juice, dragon juice, pear juice, hot cappuccino, cold cappuccino, hot milk coffee, cold milk coffee, cold milk tea, hot egg tea, and hot/cold tea. (2) Menu that has profitability of pecel lele, pecel ayam, chicken soy sauce, red chilli duck, ayam goreng cianjur, ayam rica-rica, green chili duck, apple juice, avocado juice, guava juice, orange juice, Soursop juice, dragon juice, pear juice, star fruit juice, melon juice, turquoise eggplant juice, papaya juice, strawberry juice, tomato juice, and carrot juice. (3) The menu positions on the four box analysis of the star groups are pecel lele, pecel ayam, apple juice, avocado juice, guava juice, orange juice, mango juice, soursop juice, dragon juice, and pear juice. The menus included in the plowhorse group are soto betawi, fried rice, hot cappuccino, cold cappuccino, hot milk coffee, cold milk coffee, cold milk tea, hot egg tea and hot/cold tea. The menus included in the puzzle group are chicken soy sauce, red chilli duck, chicken fried cianjur, chicken rica-rica, green chili duck, star fruit juice, melon juice, turquoise eggplant juice, papaya juice, cucumber juice, and strawberry juice. Menus included in the group of dogs are fried noodles, boiled noodles, fried rice noodles, fried kwetiau, tofu/tempe, ampela, hot ginseng coffee, cold ginseng coffee, hot milk tea, and cold egg teaKeywords: Popularity, Profitability, Menu Engineering